Law enforcement in the trauma bay: a survey of members of the American Academy for the Surgery of Trauma - Erin C Hall; Sara F Jacoby; Jessica H Beard; Utsha Khatri; Elinore J Kaufman; Rucha Alur; Jamie Song (Trauma Surgery & Acute Care Open)
Background Trauma patients frequently come into contact with law enforcement officers (LEOs) during the course of their medical care, but little is known about how LEO presence affects processes of care. We surveyed members of the American Association for the Surgery of Trauma (AAST) to assess their perspectives on frequency, circumstances, and implications of LEO presence in trauma bays nationwide.Methods Survey items addressed respondents’ experience with the frequency and context of LEO presence and their perspectives on the impact of LEO presence for patients, clinical care, and public safety. Respondent demographics, professional characteristics, and practice setting were collected. The survey was distributed electronically to AAST members in September and October of 2020. Responses were compared by participant age, gender, race, ethnicity, urban versus rural location using χ2 tests.Results Of 234 respondents, 189 (80.7%) were attending surgeons, 169 (72.2%) identified as white, and 144 (61.5%) as male. 187 respondents (79.9%) observed LEO presence at least weekly. Respondents found LEO presence was most helpful for public safety, followed by clinical care, and then for patients. Older respondents rated LEO presence as helpful more often than younger respondents regarding the impact on patients, clinical care, and public safety (p<0.001 across all domains). When determining LEO access, respondents assessed severity of the patient’s condition, the safety of emergency department staff, the safety of LEOs, and a patient’s potential role as a threat to public safety.Conclusions Respondents described a wide range of perspectives on the impact and consequence of LEO in the trauma bay, with little policy to guide interactions. The overlap of law enforcement and healthcare in the trauma bay deserves attention from institutional and professional policymakers to preserve patient safety and autonomy and patient-centered care.Level of evidence IV, survey study.